DGAT1 gene polymorphism and their association with fat deposition and carcass quality in Pasundan cattle of Indonesia - DUDI DUDI; NENA HILMIA; ISYANA KHAERUNNISA; ANDI MUSHAWWIR (Society for Indonesian Biodiversity, 2023)
Abstract. Dudi D, Hilmia N, Khaerunnisa I, Mushawwir A. 2023. DGAT1 gene polymorphism and their association with fat deposition and carcass quality in Pasundan cattle of Indonesia. Biodiversitas 24: 4202-4208. The bovineAcyl-CoA: Diacylglycerol O-acyltransferase 1 (DGAT1) gene is crucial to milk and meat quality in cattle. The K232A DGAT1 mutation was broadly used as a milk and meat quality genetic marker. Pasundan cattle are Indonesian local cattle from West Java. These local cattle have adapted to the tropical environment, environmental factors are not obstructing their development. The DGAT1 gene polymorphism information and their contribution to fat deposition and carcass quality in Pasundan cattle is very limited. The objective of this study was to examine the genetic polymorphism of the K232A DGAT1 gene and its association with fat deposition and carcass quality in Pasundan cattle population. The gene polymorphisms were identified using PCR, and direct sequencing to discover a single nucleotide polymorphism (SNP). All sequencing results (ABI trace files) were analyzed in FinchTV, BioEdit, and Molecular Evolutionary Genetic Analysis (MEGA) 6.0. Genotyping was performed on 80 Pasundan cattle. In comparison, Ongole-Grade (n=5), Bali (n=2), Simmental (n=2), Limousin (n=2), Madura (n=2), and Pesisir (n=2) were also used in this study. Their association with fat deposition and carcass quality was evaluated on seven heads of AK genotype and 23 heads of KK genotype. According to the sequencing result, two SNPs were found at g.201G>A and g.202C>A, respectively. The K232A DGAT1 locus was polymorphic in Pasundan cattle population with the K and A allele frequencies of 0.956 and 0.044, respectively. In addition, DGAT1 gene polymorphisms are not associated with back fat thickness, longissimus dorsi area, rump area, and intramuscular fat.